Improving Work Readiness and Career Planning for Internship Students from Poco Ranaka and Lamba Leda Vocational High Schools at the Watumori Plantation - Lena Ellitan; Lina Anatan (CV. Ulil Albab Corp, 2026)
This Community Service activity aims to improve the work readiness and career planning of intern students from Poco Ranaka and Lamba Leda Vocational High Schools who are undergoing industrial work experience at the Watumori Plantation. The activity took place on May 24, 2025, at the Watumori Plantation. This activity included providing job competency training, developing soft skills, and guiding the interns in career planning, using counselling, interactive discussions, and simulations of real-world work situations. Through this activity, students are expected to understand the demands of the workplace, develop a professional attitude, and design career development strategies aligned with their interests and abilities. The results of the activity indicate increased student motivation and readiness for the workplace, as well as an increased understanding of the importance of early career planning. This community service is expected to serve as a practical training model for interns in the plantation sector and related industries.